Re-Purposing the Library Space in the Digital Era: A study - Panigrahi, Sushant (Journal of Information and Knowledge, 2021)
Purpose: The round the clock availability of information sources, high speed internet in the 4G era, low cost of data download, cheaper cost of laptops and smart phones are factors impacting the purpose users’ visit to libraries. Library users visit less for the purposes of issue/return, browsing and searching information in the print holdings of the library. The users are rather spending more time in study, accessing e-resources, socialize with friends, discuss with peer group, etc. in the library building. The libraries in the developed countries have already recognized the need of the hour and re-designed their space to create a variety of reading space, creative space, Makers space, quiet space, etc. in the existing library buildings. But libraries in higher education institutions in India are yet to seriously consider the users’ need with respect to library space use. The present study has been conducted to find the users’ opinion and views to re-purpose the library space to meet their need. Research Methodology: Survey method has been used gather the views and opinion of library users. Printed questionnaires were distributed to the users present in the reading halls of the library. Due to paucity of time the research was limited to Jawaharlal Nehru University, New Delhi and Delhi University, New Delhi. Online questionnaires were distributed to faculty members as they visit the library less frequently. The collected data was analyzed with MS-EXCEL and hypothesis tested using Kruskal Wallis test. Findings: Students and Research Scholars visit daily and spend more than four hours in the library building. They use their time in study, accessing e-resources in the reading hall of the library than any other place. The views of the all the users suggest that the library should have wi-fi facilities, power point for plug laptops and mobile phones, washroom near reading hall, quiet space, and clean ambient environment for longer hour study in the library building. Originality: The study is useful for Librarians for designing and refurbishing their library space.